Multidisciplinary teams as "technical reference" devices in mental health in caps and care management: an integrative literature review (Research, Society and Development, 2021)
We aim to carry out an integrative literature review about care management and multidisciplinary teams in mental health studies published in journals between the years 2015 and 2020. Methodologically, an integrative literature review was used, establishing a guiding question: the multidisciplinary team as devices “ reference technicians ”in mental health at CAPS have training for the management of mental health care as they have knowledge about their duties? The databases were defined: LILACS, SciELO, PubMed Central and MEDLINE and descriptors combined with Boolean operators: CAPS” or “gestão do cuidado” and “Técnicos de referência” and “equipe multidisciplinar” and “saúde mental” and “Reference technicians” and “Multidisciplinary team” and “Mental health” and “Care management”. After that, we established the inclusion exclusion criteria; categorization of studies and data extraction; evaluation of studies included in the review; discussion and interpretation of results and synthesis of the information evidenced in the articles. As a result, 147 scientific articles were reviewed and only 15 were part of this study, thus defining two subcategories for analyzing the articles: unfavorable and unfavorable aspects in relation to the management of care and the multidisciplinary team as mental health devices in CAPS. We conclude that a unique interaction and the involvement of all members of the multidisciplinary team as technical devices of reference in the CAPS is of paramount importance in adopting more effective measures. Teamwork can become differentiated to the point of looking at the patient as a whole and providing more humanized care.